Political Exile and Development of Local Studies in Northern Russia in 19th - early 20th Centuries: Experience of Rethinking - A M Pashkov (RUDN Journal of Russian History, 2011)
The article analyses the role of political exiles in the development of Local studies in Northern Russia in the 19th - early 20th centuries. The author notes that the process of local intelligentsia formation took place in this period. Local intelligentsia became actively involved in Local studies, and, therefore, the contribution of political exiles into the Local studies gradually decreased. Political exiles played the most important role in Local studies in Northern Russia only in the years 1825-1861. In 1861-1904 their contribution decreased, and in 1905-1917 political exiles activity constituted a small part of the whole Local studies.